Parcels and Peppers: Savory Ideas for Addressing Vacancy in St. Louis - Swehla, Tyler; Taylor, Morgan; Shy, Kelsie; Jagles, Emily; Allen, Taylor; Fiala, Abigail; Jackman, Sarah; Rose, Katelyn; Vallo, Laura; Stucki, Lindsay; Knight, Jonathan; Tucker, Tyler; et al. (Kansas State University, 2015)
Beginning in the 1950s, many American cities experienced significant population decline in their urban core. The reasons for decline include local, regional and federal policies, housing preferences, social issues, racial discrimination, transportation options, economic trends, quality of public schools, and many other interrelated complex variables. While some downtown areas have experienced a significant renaissance over the past 10 or 20 years, others remain relatively empty in the middle, so-called “Shrinking Cities” or “Legacy Cities.” The City of St. Louis experienced a 62% decline in population from its peak in 1950, and now has one of the highest rates of property vacancy in the nation. While crime rates soar and educational attainment lags in areas of high vacancy, there are reasons for hope. The City is considering redevelopment projects in vacancy-plagued neighborhoods, local change-makers are investing in their communities, and one district has begun reversing the trend of depopulation, albeit at a very small scale. However, with nearly 25,000 vacant parcels in the City, there is an urgent need for ideas and approaches to transform vacant land, from the scale of single lots to entire urban districts. This book presents planning and design strategies for understanding vacancy conditions, a range of ideas for repurposing vacant property, and a variety of methods for engaging people in a planning and design dialogue about vacancy. Throughout the book we use a metaphor of “spiciness” to communicate a gradient of ideas, inspired by the chili pepper shape of St. Louis’ city boundary. Kansas State University graduate students prepared the book as the final product of the 2015 Community Planning and Design Studio, taught by Associate Professors Blake Belanger and Howard Hahn. The 18 students were midway through a Master’s of Landscape Architecture degree in the Department of Landscape Architecture and Regional & Community Planning. We worked with K-State’s Technical Assistance for Brownfields Communities, the City of St. Louis, and representatives from the White House Strong Cities, Strong Communities Initiative, which the Obama Administration tasked with providing technical advice and expertise to seven cities with the intent of regaining economic footing. Our initial methods included researching the “shrinking cities” phenomena and ideas for addressing vacancy through a variety of texts, articles, and case studies; familiarizing ourselves with conditions in St. Louis through historical texts, periodicals, meetings with project partners, and a field visit; and extensive critical mapping including demographic, economic, social, infrastructural, and physiographic conditions. Building upon our collective knowledge base, we then completed a weeklong divergent-thinking exercise to imagine as many ideas as possible. The class then divided into four teams, each focusing on a different aspect of the final product: communication, classification/typology, ideas for repurposing vacant parcels, and community participation. The primary outcome is a set of five tools for action that can be used by a spectrum of community actors, from local residents to high-level decision-makers and developers. The first tool is an encyclopedia of over 60 ideas for repurposing vacant land and salvageable abandoned buildings. The Encyclopedia of Ideas, which ranges from mild ideas already being implemented to highly ambitious alterations in urban land use, might inspire action from a variety of players at a variety of scales. The second tool, the Vacancy Conditions Worksheet, empowers residents and landowners to evaluate vacant lots and match appropriate ideas for action. The third tool proposes launching a new website and social media campaign for connecting people with a common purpose and collecting citizens’ ideas for change. Information Collection is the fourth tool, which proposes different methods for gathering relevant data about vacant lots to fill gaps in the city’s databases. Lastly, and perhaps most significant, the Vacancy Evaluation Framework provides a holistic and sophisticated armature for connecting the other four tools and assisting decision-makers and large-scale investors to implement vacant land repurposing strategies. We hope the work contained herein will be inspirational to residents, planners, scholars, activists, non-profits, and change-makers in St. Louis and other Legacy Cities.
Keywords: Shrinking cities; Legacy cities; Landscape architecture; Urban planning; Vacancy typology; Repurposing vacant land; Community participation